2019
DOI: 10.15252/emmm.201809709
|View full text |Cite
|
Sign up to set email alerts
|

MET mutation causes muscular dysplasia and arthrogryposis

Abstract: Arthrogryposis is a group of phenotypically and genetically heterogeneous disorders characterized by congenital contractures of two or more parts of the body; the pathogenesis and the causative genes of arthrogryposis remain undetermined. We examined a four‐generation arthrogryposis pedigree characterized by camptodactyly, limited forearm supination, and loss of myofibers in the forearms and hands. By using whole‐exome sequencing, we confirmed MET p.Y1234C mutation to be responsible for arthrogryposis in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In Family 2, IV:2, III:10, and III:11 were subjected to whole‐exome sequencing. As previously reported (Zhou et al, 2019), we annotated and filtered variants and kept variants that were novel in dbSNP. Polyphen‐2, Mutation Taster, and Genomic Evolutionary Rate Profiling (GERP) were then used to predict the potential functional effects of these mutations.…”
Section: Resultsmentioning
confidence: 99%
“…In Family 2, IV:2, III:10, and III:11 were subjected to whole‐exome sequencing. As previously reported (Zhou et al, 2019), we annotated and filtered variants and kept variants that were novel in dbSNP. Polyphen‐2, Mutation Taster, and Genomic Evolutionary Rate Profiling (GERP) were then used to predict the potential functional effects of these mutations.…”
Section: Resultsmentioning
confidence: 99%
“…The affected residue is adjacent to the tyrosine mutated in the previously reported Chinese family (Zhou et al, 2019 ). Functional studies on MET p.Y1234 mutation showed the inability of the mutant MET receptor to phosphorylate residues Y-1234/1235, Y-1349, and Y-1356 in response to HGF treatment, resulting in failure of c-MET activation and decreasing of its kinase activity, with the consequent impairment of the HGF-MET signaling (Zhou et al, 2019 ). A similar pathogenic mechanism is then anticipated for the mutation identified in our family.…”
mentioning
confidence: 84%
“…In 2019, a study reported a single four-generation Chinese family with arthrogryposis with only upper limb involvement and a missense mutation of the MET gene affecting the Tyrosine residue 1234 (p.Tyr1234Cys) (Zhou et al, 2019 ). The authors generated a Met p.Y1232C (corresponding to the p.Y1234C in humans) transgenic mouse model identifying a defective migration of muscle progenitor cells and an impaired proliferation of secondary myoblasts.…”
mentioning
confidence: 99%